Programmable fir filters - Duan, Hua. (2013)
In this project, the student needs to help to design software to enable the control of a chip based RF FIR filter. The student needs to use the knowledge of digital filter design and programming skills. The impulse response of a finite impulse response (FIR) filter is of finite duration in signal processing, because it is settled to zero in finite time. FIR filters can be discrete-time or continuous-time, and digital or analog. The input signal x and its impulse response b determines the output y of a linear time invariant system. The student needs to use LabVIEW to design a program to control the voltage of DAC board, then DAC board supplies voltage to Variable Optical Attenuator (VOA). VOA then controls the coefficient of each branch of filter in order to meet the requirement of FIR filter.